DESCRIPTION OF THE NUTRITIONAL STATUS OF STUDENTS IN SD NEGERI 3 PELIATAN, SUBDISTRICT UBUD, GIANYAR - Hapsari, Ayu Indah; Antari, Putu Yuniadi; Ani, Luh Seri (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Elementary school student are the group of student that potentialy having problem with nutrition due to their eating patern and development status . The cases of malnutrition in U bud is still highly noted even if Ubud is kown as well-developed subdistrict. T he aimed of t he study is to d escript the nutritional status and other factors related to among the students of SD Negeri 3 Peliatan, Subdistrict Ubud, Gianyar. This study was done on August 19 th 2011 until August 20 th 2011 and th e study design was a cross-sectional. Subjects were the grade 5 th and 6 th students with a total of 70 student, were chose n by quota sampling technique . Every subject was asked to administer questionnaire, to get the informaton on characteristic, eating pattern and breakfast habit. Antropometric measurements were done to gain the nutritional status of sampel. History of low birth weigh t was collected from the parents through administering self-administered questionnaires . The data was analysed descriptive ly . R esult show ed that subjects tend to have high malnutrition cases, in whom 25.7% were undernutrition a nd 24.3% were overnutrition 24 . 3 %. Majority of subjects who have good nutritional status were those who admitted to have balanced eating pattern and breakfast habit. In addition, subjects with good nutrition status tended to have good academic scores and those with history of low birth weight seemed to have good and over nutritional status. As the students of SD Negeri 3 Peliatan seemed to have remarkable problem of malnutrition, it is suggested to inform their parents regarding the best eating pattern and to emphasize the importance of berakfast habit to achieve and maintain the good nutritional status for their children . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: nutritional status, eating pattern, low birth weight